Perencanaan Pemeliharaan 32.000 Jam di PLTMGU Lombok untuk Optimalisasi Equivalent Availability Factor - Rudianto, Kusnendar Trianto; Patra, Oviyan (Jurnal Pendidikan Indonesia, 2025)
PT. Wartsila Indonesia, as the manager of the Lombok Gas and Steam Engine Power Plant (PLTMGU) has an obligation to maintain an Equivalent Availability Factor (EAF) above 90%. In 2024, EAF will be recorded at 96.97%, with a total outage of 3,726 hours due to Planned Outage (PO) and Force Outage (FO). For 2025, EAF is predicted to be 90.02% with a PO of 7,958 Hours. The planned duration of the PO for 32,000 hours of maintenance is 18 days or 432 hours. The total number of machines that will carry out maintenance of these 32,000 hours is nine Wartsila machines W20V34DF. This study aims to plan a 32,000-hour maintenance activity schedule using the Work Breakdown Structure (WBS) method, and the Critical Path Method (CPM). The study successfully shortened the planned maintenance duration from 18 days (432 hours) to 15 days (345 hours), saving 87 hours per machine. This reduction in maintenance duration can increase EAF and anticipate FO by providing a UOH allocation of 274 hours. With this allocation, the EAF Prediction in 2025 increased to 90.66% beyond the initial prediction. These results confirm the importance of careful planning and management of maintenance schedules to maintain operational sustainability and improve power plant performance.